2022
DOI: 10.3390/ijerph191912422
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 Vaccines on Reducing the Risk of Long COVID in the Real World: A Systematic Review and Meta-Analysis

Abstract: The coronavirus disease 2019 (COVID-19) is still in a global pandemic state. Some studies have reported that COVID-19 vaccines had a protective effect against long COVID. However, the conclusions of the studies on the effect of COVID-19 vaccines on long COVID were not consistent. This study aimed to systematically review relevant studies in the real world, and performed a meta-analysis to explore the relationship between vaccination and long COVID. We systematically searched PubMed, Embase, Web of science, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
86
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(102 citation statements)
references
References 47 publications
10
86
0
6
Order By: Relevance
“…19,20,21,22 Gompertzian Analysis has found that unlike Gompertzian Lethality, Long COVID occurs at relatively equivalent rates across ages (APPENDIX-FIGURE 40). 23,24 Vaccination has been found to protect against Long COVID , (APPENDIX-FIGURE 41), 25,2627,28 with protection increasing with each additional dose, 29 although the data so are far not sufficient to determine which symptoms are prevented, and most importantly, to what degree pandemic associated excess mortality is reduced, if at all, but vaccination. 30,31 Clearly, this remains a problem of high importance, which should be decipherable by Gompertzian Analysis .…”
Section: Resultsmentioning
confidence: 99%
“…19,20,21,22 Gompertzian Analysis has found that unlike Gompertzian Lethality, Long COVID occurs at relatively equivalent rates across ages (APPENDIX-FIGURE 40). 23,24 Vaccination has been found to protect against Long COVID , (APPENDIX-FIGURE 41), 25,2627,28 with protection increasing with each additional dose, 29 although the data so are far not sufficient to determine which symptoms are prevented, and most importantly, to what degree pandemic associated excess mortality is reduced, if at all, but vaccination. 30,31 Clearly, this remains a problem of high importance, which should be decipherable by Gompertzian Analysis .…”
Section: Resultsmentioning
confidence: 99%
“…The widespread vaccination approach has been a game-changer in reducing the spread as well as the severity of COVID-19 disease in adults [ 151 , 152 ]. Vaccinating pregnant women is a vital strategy to reduce the risk of SARS-CoV-2 transmission to the fetus and newborn baby.…”
Section: Strategies For Preventing Perinatal Covid-19mentioning
confidence: 99%
“…In einer rezent publizierten Metaanalyse mit insgesamt über einer Million Patient:innen aus 18 Studien fand man, dass die COVID-Schutzimpfung das Risiko für Long COVID unabhängig vom Zeitpunkt der Impfung verringert [ 35 ]. Das heißt, selbst nach einer bereits abgelaufenen COVID-19-Erkrankung stellt das Impfen danach noch einen Schutzfaktor für Long COVID dar.…”
Section: Die Impfung Schützt Vor Long Covidunclassified
“…Auch in einer größeren retrospektiven Studie mit 14.104 Patientinnen stellte man fest, dass maternale Mortalität und schwerwiegende Schwangerschaftskomplikationen (z. B. hypertensive Störungen, postpartale Blutungen) bei SARS-CoV-2-infizierten Frauen 40 % häufiger auftraten als bei seronegativen Frauen [ 35 ].…”
Section: Risikofaktoren Und Therapie Für Long Covid In Der Schwangers...unclassified